Observations of Rayleigh waves in Mexico City Valley during the 19 September 2017 Puebla–Morelos, Mexico earthquake. Issue 2 (December 2020) - Heresi, Pablo; Ruiz-García, Jorge; Payán-Serrano, Omar; Miranda, Eduardo
This article discusses the principal features of Rayleigh surface waves generated by basin-edge effects in Mexico City during the Mw 7.1 19 September 2017 Puebla–Morelos, Mexico earthquake. Rayleigh waves were extracted from ground motions recorded at 12 stations in Mexico City. We used a recently proposed method for extracting surface waves, where the earthquake record is filtered based on the normalized inner product of the Stockwell transform of the three-component earthquake recordings. Results of this study reveal that basin-edge effects produced strong Rayleigh waves, particularly at certain stations, with frequencies that are mainly between 0.2 and 0.9 Hz, which is consistent with previous frequency ranges reported in the literature. Evidence of higher-mode Rayleigh waves was found at all stations located on soft soil sites, even at stations that are more than 1 km away from the basin edges. It was also observed that peak acceleration spectral ordinates of the retrograde component of the extracted Rayleigh waves at two stations exceeded the design spectral ordinates of the 1976 and 2004 editions of the Mexico City Seismic Provisions.